2015
DOI: 10.1177/0091026015607107
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Measurement of the Work Values of Chinese Civil Servants

Abstract: A stable and efficient team of civil servants facilitates high performance for their government. With further standardization of civil servants' salary and bonuses, the tendency of turnover becomes apparent in public service. Under this context, it seems to be a critical issue regarding how to reduce the turnover intention and how to motivate civil servants to improve their work performance. Hangzhou City in China has historically demonstrated high performance and a low turnover rate. We developed an instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It suggests a strong benefit‐oriented motivation system for them, given their cardinal value types of Hedonism and Security. Particularly, considering the recent shrinking of employee benefits in Chinese public organisations (Zhang & Chen, ), a new and proper benefit system should be considered if these organisations intend to retain their employees. From the perspective of recruitment, the stability and benefits should be communicated clearly and loudly to potential employees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggests a strong benefit‐oriented motivation system for them, given their cardinal value types of Hedonism and Security. Particularly, considering the recent shrinking of employee benefits in Chinese public organisations (Zhang & Chen, ), a new and proper benefit system should be considered if these organisations intend to retain their employees. From the perspective of recruitment, the stability and benefits should be communicated clearly and loudly to potential employees.…”
Section: Discussionmentioning
confidence: 99%
“…These students are current and prospective employees in Chinese public organisations. As the country has been experiencing fundamental public organisation reforms, their value profiles could be profoundly affected (Zhang & Chen, ). Particularly, there are three types of public organisations in China: the core public service, parapublic sectors, and public enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Prospect theory revealed that managers did not always make rational decisions because the complexity of preferences arose from fact that experience values and decision values were not always perfectly matched (Kahneman & Tversky, 1984). Thus, values preferences have been a matter of widespread concern (Choi & Chung, 2017; Connor & Becker, 2003; Song, Kwon, & Cha, 2017; Van der Wal & Huberts, 2008; Van Ryzin, 2016; Zhang & Chen, 2015). Theoretical and empirical studies of public servants’ values have been explored in the field of public administration and political science (Ciuk, 2017; Högström, Davoudi, Löfgren, & Johnson, 2016; Schuh, 2006; Schwartz et al, 2014).…”
Section: Public Values and Pvpsmentioning
confidence: 99%
“…In proposing priorities for marketing research, Ostrom et al (2010) identify measuring and optimizing the value of service as key areas for research, although the focus is on measurement and metrics rather than on understanding what value actually means. Elsewhere, attempts to measure value are proposed in the development of an assessment model (Xing et al , 2013) and in a study of municipal workers (Zhang and Chen, 2015). In other research, Ojasalo (2010) highlights the importance of customers’ experiences in understanding value and in the value creation process.…”
Section: Introductionmentioning
confidence: 99%